Teaching space-group diagrams to chemistry students through a peer-tutoring approach - Zheng, Shao-Liang; Campbell, Michael G. (Acta crystallographica. Section E, Crystallographic communications, 2021)
Peer tutoring is a teaching strategy that offers a creative way of getting students more involved and accountable for their own learning in college-level chemistry courses. The authors have found that the ` Symmetry and Space Group Tutorial ' [Jasinski & Foxman (2007). Symmetry and Space Group Tutorial , V1.55. http://people.brandeis.edu/~foxman1/teaching/indexpr.html] lends itself well to a peer-tutoring approach in a crystallography course for chemistry students. This in-class activity provides an opportunity for students to learn space-group diagrams, understand basic symmetry concepts, organize what they have learned, and explain it to their peers, which leads to a deeper overall understanding of the subject. We report on our experience in planning peer tutoring, advise on best practices, and demonstrate the positive impact on student learning and engagement.